The newcomers : finding refuge, friendship, and hope in an American classroom - Thorpe, Helen, 1965- (New York : Scribner, 2017)
Traces the lives of twenty-two immigrant teens throughout the course of a year at Denver's South High School who attended a specially created English Language Acquisition class and who were helped to adapt through strategic introductions to American culture.
Keywords: Teenage immigrants -- Education (Secondary) -- Colorado -- Denver; Teenage refugees -- Education (Secondary) -- Colorado -- Denver; English language -- Study and teaching -- Foreign speakers; Teenage immigrants -- Colorado -- Denver; Teenage refugees -- Colorado -- Denver; Americanization; Immigrants -- Education -- Denver (Colo.); Refugees -- Education -- Denver (Colo.); English as a second language; Immigrants -- Denver (Colo.); Refugees -- Denver (Colo.); Americanization